An improved PCR‐CTPP assay for the detection of ADH1B Arg48His polymorphism. Issue 2 (28th June 2017) - Jiang, Shupeng; Tong, Yongqing; Zhao, Rui; Xiong, Ge; Qiao, Bin; Li, Yan
Abstract : Background: ADH1B Arg48His polymorphism is associated with the development of alcohol‐related diseases. In this study, we aimed to explore an improved polymerase chain reaction with confronting two‐pair primers (PCR‐CTPP) assay for the detection of ADH1B Arg48His polymorphism. Methods: A mismatch was introduced at the 3′ end of each of the two allele‐specific to increase the specificity of the reaction. But beyond that, a new mismatch at‐3 positions of outer primers was designed to decrease the efficiency of the aforementioned primers and depresses the amplification of an internal nonspecific DNA control. A total of 180 samples from healthy volunteers Han Chinese were tested to evaluate this new assay. Results: The protocol of PCR‐CTPP was successful for genotyping of ADH1B Arg48His . The results from the improved PCR‐CTPP assay were confirmed by Sanger sequencing, and correct genotyping rates were 100%.The genotype frequencies were 49.44% (89 cases) for His/His, 46.67% (84 cases) for Arg/His, and 3.89% (seven cases) for Arg/Arg respectively. Conclusions: This improved PCR‐CTPP assay is simple, rapid, cost‐effective, and reliable, specific for the detection of ADH1B Arg48His polymorphism in most clinical diagnostic laboratories.